Pharmacokinetics and pharmacodynamics of continuous-infusion meropenem in pediatric hematopoietic stem cell transplant patients. - Cojutti, Piergiorgio; Maximova, Natalia; Pea, Federico (Antimicrob Agents Chemother, 2015)
This study explored the pharmacokinetics and the pharmacodynamics of continuous-infusion meropenem in a population of pediatric hematopoietic stem cell transplant (HSCT) patients who underwent therapeutic drug monitoring. The relationship between meropenem clearance (CLM) and estimated creatinine clearance (CLCR) was assessed by nonlinear regression. A Monte Carlo simulation was performed to investigate the predictive performance of five dosing regimens (15 to 90 mg/kg of body weight/day) for the empirical treatment of severe Gram-negative-related infections in relation to four different categories of renal function. The optimal target was defined as a probability of target attainment (PTA) of ≥90% at steady-state concentration-to-MIC ratios (C SS/MIC) of ≥1 and ≥4 for MICs of up to 8 mg/liter. A total of 21 patients with 44 meropenem C SS were included. A good relationship between CLM and estimated CLCR was observed (r (2) = 0.733). Simulations showed that at an MIC of 2 mg/liter, the administration of continuous-infusion meropenem at doses of 15, 30, 45, and 60 mg/kg/day may achieve a PTA of ≥90% at a C SS/MIC ratio of ≥4 in the CLCR categories of 40 to <80, 80 to <120, 120 to <200, and 200 to <300 ml/min/1.73 m(2), respectively. At an MIC of 8 mg/liter, doses of up to 90 mg/kg/day by continuous infusion may achieve optimal PTA only in the CLCR categories of 40 to <80 and 80 to <120 ml/min/1.73 m(2). Continuous-infusion meropenem at dosages up to 90 mg/kg/day might be effective for optimal treatment of severe Gram-negative-related infections in pediatric HSCT patients, even when caused by carbapenem-resistant pathogens with an MIC of up to 8 mg/liter.